CONTENT ANALYSIS OF STUDENTS' ARGUMENTS BASED ON MATHEMATICAL LITERACY AND CREATION ABILITY : ANALISIS ISI ARGUMEN SISWA BERDASARKAN LITERASI MATEMATIKA DAN KEMAMPUAN KREASI - Nasrullah (MaPan : Jurnal Matematika dan Pembelajaran, 2022)
This study aims to show the content of students' argumentation in building their creative reasoning and the relationship between argumentation content and students' mathematical literacy skills. The type of research applied is descriptive qualitative research involving 27 junior high school students in Toli-Toli City, Central Sulawesi. The research instrument used was a like-mathematical literacy test and an assessment rubric. The collected data were analyzed using qualitative content analysis which was used to analyze text data. The results of the research show that 1) The content of students' arguments in building their creative reasoning is supported by using simple statements, complex statements, completed by syntax or no syntax in building mathematical arguments, and 2) the ability of students to show their argumentation in the problem solving is the level of their capacity to interpret and to represent their knowledge and learning experience related with the problem. The breadth and depth of content of students' mathematical literacy give them the flexibility to argue. Students' mathematical literacy ability by simply giving simple statements has a different breadth and depth than those who are able to give complex statements. Likewise with the shrewdness of using syntax in constructing problem-solving plans.